Development of â€œKenaladaâ€ Animation Media as A Learning Media During The Covid-19 - Hidayati, Awanis (International Journal of Applied Guidance and Counseling, 2022)
This study aims to develop animation media in improving student learning outcomes in learning the characteristics and competencies of Elementary School Children Materials for Elementary School Children's Needs (KENALADA) for Guidance and Counseling Study Program students, FKIP UNTAN Pontianak. Animation media is one example of the use of technology in supporting the learning process. This media can increase the enthusiasm and attention of students to learn, especially during the pandemic when all learning is required online. This study uses the Research and Development (R&D) method using five stages, namely the ADDIE Model: Analysis, Design, Development, Implementation, and Evaluation. The form of experiment in this research is posttest only design. This study used the entire population as a sample, namely the Guidance and Counseling Study Program class A as the experimental class and the Guidance and Counseling Study Program in class B as the control class. The experimental class in its learning uses animation media and the control class in its learning does not use animation media. The test results in the experimental class showed a higher score than the class that did not use animation media, so that animated video media was effective in learning.